Histologic Changes In Recreational Drug Misuse - Milroy, Christopher M. (Acad Forensic Pathol, 2018)
Use of recreational drugs is associated with a number of histologic changes. These may be related to the method of administration or due to systemic effects of the drugs. This paper reviews the histopathological features seen following recreational drug use. With injection, there may be local effects from abscess formation and systemic effects may result in amyloidosis. Injections have been associated with necrotizing fasciitis, anthrax, and clostridial infections. Systemic effects include infective endocarditis, with the risk of embolization, and abscesses may be seen in organs in the absence of infective endocarditis. Viral complications of injection include hepatitis and human immunodeficiency virus (HIV) infection. Injecting crushed tablets can result in intravascular granulomata in the lungs. Smoking drugs is associated with intraalveolar changes, including blackand brown-pigmented macrophages in crack cocaine and cannabis smoking, respectively. Snorting may result in intraalveolar granulomata forming when crush tablets are used and there may be systemic granulomata. Stimulants are associated with cardiovascular and cerebrovascular pathology, including contraction band necrosis and myocardial fibrosis, as well as coronary artery dissection. Stimulants may cause hyperpyrexia and rhabdomyolysis, which may be associated with changes in multiple organs including myoglobin casts in the kidney. Opioids cause respiratory depression and this can be associated with inhalational pneumonia and hypoxia in other organs if there is resuscitation and a period of survival. Ketamine use has been associated with changes in the urothelium and the liver. This paper reviews histology changes that may be seen in drug-related deaths using illustrative cases.